Biological differences and social equality: implications for social policy ; [papers based on a Summer Inst. on Biological Diversity and Social Equality held at the Center for Advanced Study in Behavioral Sciences at Stanford durin July and Aug. 1978] - Darrough, Masako N.; Blank, Robert H. (Greenwood Pr., 1983)
The reality and significance of human races / Richard A. Goldsby -- Search for equity on the planet difference / Nancy R. Hauserman -- Evolution, ethics, and equality / Stephen L. Zegura, Stuart C. Gilman, and Robert L. Simon -- The issue of inequality / Stuart C. Gilman -- The liberal conception of equal opportunity and its egalitarian critics / Robert L. Simon -- Biological differences and economic equality / Masako N. Darrough -- Social equality and ethnic identity / Sandra L. Schultz -- Social equality and infectious disease carriers / Baruch S. Blumberg -- Societal responsibility and genetic disease / Robert H. Blank -- Intelligence theory and the race-IQ controversy / John G. Borkowski